ENERGY EFFICIENCY OF THE MINERAL FERTILIZER APPLICATION IN CROP PRODUCTION - Dimitrijević, Aleksandra; Gavrilović, Marija; Mileusnić, Zoran; Miodragović, Rajko (Journal on Processing and Energy in Agriculture, 2020)
Efficiency of the primary agricultural production is under constant analysis regarding energy, economy and ecology. Regardless the innovation and technical progress, engineers and researchers are still looking for production system that will make primary agricultural production more energy efficient and ecology sustainable. This paper gives the results on the energy consumption and energy efficiency of crop production, emphasizing the importance of the mineral fertilizers use and their influence on the overall energy consumption. Results show that mineral fertilizers participate in the total energy consumption in crop production, from 40.53% (seed sunflower) up to 55.19% (maize). Statistical analysis showed that there is a correlation between energy input through the fertilizers and yield. The regression analysis showed that there is a positive relation between the crop yield and energy used through the fertilizer in all cases except in case of wheat.
Keywords: mineral fertilizers, crop production, energy consumption, energy efficiency